1998
DOI: 10.3233/ves-1998-8301
|View full text |Cite
|
Sign up to set email alerts
|

A Link-Segment Model of Upright Human Posture for Analysis of Head-Trunk Coordination

Abstract: Sensory-motor control of upright human posture may be organized in a top-down fashion such that certain head-trunk coordination strategies are employed to optimize visual and/or vestibular sensory inputs. Previous quantitative models of the biomechanics of human posture control have examined the simple case of ankle sway strategy, in which an inverted pendulum model is used, and the somewhat more complicated case of hip sway strategy, in which multisegment, articulated models are used. While these models can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…This information provides assistance to researchers and clinicians deciding which types of support surface and visual conditions are needed to target specific joints during single-leg stance testing and rehabilitation procedures. Although the assumption that the body sways as an inverted pendulum about the ankle during quiet double-leg stance has been widely used, 31 multiple studies 21,[31][32][33] have shown that the body does not move as a rigid segment but rather as a multilink structure. For example, Day et al 21 revealed that, in the sagittal plane, the most angular movement occurred between the trunk and upper leg, independent of stance width.…”
Section: Resultsmentioning
confidence: 99%
“…This information provides assistance to researchers and clinicians deciding which types of support surface and visual conditions are needed to target specific joints during single-leg stance testing and rehabilitation procedures. Although the assumption that the body sways as an inverted pendulum about the ankle during quiet double-leg stance has been widely used, 31 multiple studies 21,[31][32][33] have shown that the body does not move as a rigid segment but rather as a multilink structure. For example, Day et al 21 revealed that, in the sagittal plane, the most angular movement occurred between the trunk and upper leg, independent of stance width.…”
Section: Resultsmentioning
confidence: 99%
“…However, some investigators have successfully assessed postural balance through upper-trunk accelerometry [6,34,35]. Indeed, measuring the acceleration of the upper trunk may not only offer better sensitivity to postural response but also yield specific information about trunk dynamics [3638]. Data obtained by upper-trunk accelerometry are still sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Gatev et al (1999) showed that ankle mechanisms dominate in the sagittal plane with an almost synchronous sway of body parts. Other authors have used more complex models to represent standing (Jacobs, 1997; Lauk et al 1998; Nicholas et al 1998; Alsonso‐Sanchez & Hochberg, 2000), or have disputed the relevance of the ankle strategy and inverted pendulum model in standing (Bloem et al 2000).…”
mentioning
confidence: 99%